2022
DOI: 10.3390/v14050910
|View full text |Cite
|
Sign up to set email alerts
|

Associations and Disease–Disease Interactions of COVID-19 with Congenital and Genetic Disorders: A Comprehensive Review

Abstract: Since December 2019, the COVID-19 pandemic, which originated in Wuhan, China, has resulted in over six million deaths worldwide. Millions of people who survived this SARS-CoV-2 infection show a number of post-COVID complications. Although, the comorbid conditions and post-COVID complexities are to some extent well reviewed and known, the impact of COVID-19 on pre-existing congenital anomalies and genetic diseases are only documented in isolated case reports and case series, so far. In the present review, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 201 publications
(264 reference statements)
0
12
0
Order By: Relevance
“…9 The World Federation of Hemophilia (WFH) concluded that there is no evidence to suggest that PWH, including those on prophylaxis with traditional replacement therapy or those with haemophilia A receiving emicizumab, are at increased risk for infection with COVID-19 or for more severe disease unless they have additional well-described comorbidities such as older age (> 65 years), pulmonary or cardiovascular disease, hypertension, obesity or diabetes mellitus. 10 Whether the low rates of serious COVID-19 infection are due to some inherent degree of protection in PWH due to their coagulation state is beyond the remit of this study. However, the close interaction between PWH, their HTCs and organisations such as the WFH, the European Haemophilia Consortium (EHC), the TA B L E 1 Comorbidities in people with haemophilia A and COVID-19 infection who had serious outcomes.…”
mentioning
confidence: 93%
“…9 The World Federation of Hemophilia (WFH) concluded that there is no evidence to suggest that PWH, including those on prophylaxis with traditional replacement therapy or those with haemophilia A receiving emicizumab, are at increased risk for infection with COVID-19 or for more severe disease unless they have additional well-described comorbidities such as older age (> 65 years), pulmonary or cardiovascular disease, hypertension, obesity or diabetes mellitus. 10 Whether the low rates of serious COVID-19 infection are due to some inherent degree of protection in PWH due to their coagulation state is beyond the remit of this study. However, the close interaction between PWH, their HTCs and organisations such as the WFH, the European Haemophilia Consortium (EHC), the TA B L E 1 Comorbidities in people with haemophilia A and COVID-19 infection who had serious outcomes.…”
mentioning
confidence: 93%
“…The effect of COVID-19 vaccination on reproductive health and lactation has received plenty of attention [ 25 , 26 , 27 ]. No permanent impact of COVID-19 vaccines on reproduction-related processes such as menstruation, and female and male fertility, except for temporary disturbances in the menstruation cycle and minor drops in sperm counts immediately after vaccinations, have been found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of COVID-19 vaccinations on reproduction-related functions such as menstruation and fertility have been of concern. Several surveys including a collection of data from the VAERS have indicated potential safety concerns related to menstrual disorders in COVID-19-vaccinated young adult females [ 25 ]. Furthermore, in a retrospective study including 408 women, SARS-CoV-2 infections and COVID-19 vaccinations were indicated to influence the menstruation cycle and cause alterations to it [ 256 ].…”
Section: Effects Of Covid-19 Vaccines On Reproductive Health and Lact...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some genetic diseases and congenital anomalies are a risk factor for developing severe COVID-19 and the genetic abnormalities have also been linked to autoimmune disorders [73,74]. The studies in patients with SARS-CoV-2 have discovered some uncommon innate immunity errors in the interferon pathways and in the immune signalling circuits [74].…”
Section: Kawasaki Disease In Mis-cmentioning
confidence: 99%